Jaume I al segle XVIII: entre el teatre popular i l'erudició. - ESCARTÍ, VICENT JOSEP (Scripta, 2023)
This article tries to show how the memory of the figure of King Jaime I was maintained, in the 18th century, especially in two areas: historical scholarship -which had been dragging on since the previous century- and the presence of the character of the king and some fragments of his life, represented in some plays.